Memorandum on social insurance and allied services in their bearing on neurotic disorder / (By authority of the Council of the Royal Medico-Psychological Association)
1943 1943 1940s 19 pages 2 legislative measures are being decided on, as forecast in the House of Commons recently, the views of the medical profession and of various groups within it are certain to be sought, since considerations of health play so large a part in the whole matter ; psychiatric aspects should receive adequate attention. I. GENERAL RELEVANCE TO PSYCHIATRY. (i) Poverty and Unemployment Psychiatrists are familiar with instances of the aggravation of psychiatric illness by these stresses, and have often had their treatment frustrated by the inadequacy of available social remedies. Many studies have been carried out to assess the nature and extent of the psychological effects of long unemployment (Eisenberg and Lazarsfeld, 1936), associated as it always is on the large scale with poverty. The main conclusions may be summarized in the statement that minor psychological disturbances are frequent, but that neurosis does not usually result except among the predisposed. Where mass-unemployment strikes a whole community, as it did in Mariental, the psychological ill-effects have been so widespread as to affect many who must otherwise have been regarded as normal; these ill-effects, therefore, cannot be dismissed as merely the reactions of psychopaths. All studies emphasize how serious is the effect on juveniles, probably because they are more impressionable individuals and newcomers to the labour market. Any such effects on juveniles are likely to be far-reaching and persistent, and may modify their whole lives. Particularly for this reason a "normal" amount of unemployment cannot be regarded with complacency. Various psychological effects have been noted to follow unemployment, and the nature of some indicates that they could not be due to poverty alone. Nearly all investigators have agreed that unemployment tends to make people more unstable emotionally. They show an increased fear, a feeling of insecurity, the painful awareness of lost personal and social prestige, and a sense of hopelessness and distrust of their fellows. The suicide rate illustrates this (Dublin and Bunzel, 1933). It is hard to imagine that an adequate subsistence allowance and the prospect of certain work after six months would dispel all these. The removal of the very disturbing feeling of insecurity might be largely achieved if the ultimate machinery for re-allocation into, and stabilization in, work were efficient. But even if this machinery were satisfactory it could not completely allay the loss of self-esteem which usually follows the loss of useful work. Poverty alone seems to have been less important than insecurity and loss of prestige in causing the psychological distress ; of course, fear of poverty contributes to the insecurity. Mass unemployment was found also to cause an increasing restriction in interests and activities despite abundance of "leisure" time (Lazarsfeld, 1933). Where mass-unemployment affected only a group in an area (Paterson and Darby, 1936), there was a tendency towards the evolution of a "caste" tending to lead a separate community life, and marked by a feeling of inferiority combined with general resentment. This is a danger which has to be borne in mind in planning any scheme of social security. One important fact which has emerged from the studies of unemployment 292/847/2/174